RESISTANCE PATTERN OF EXTENDED DRUG RESISTANT SALMONELLA TYPHI IN CHILDREN - ANSWAR, .; SALAHUDDIN, A; AHMAD, A (Biological and Clinical Sciences Research Journal, 2023)
Objective: To determine the frequency of antibiotic resistance of extended drug-resistant Salmonella typhi in children. Cross-sectional observational study was conducted at Pediatric B Unit, Hayatabad Medical Complex, Peshawar, from 1st April 2021 to 30th June 2022. Approval from the institutional ethical committee was obtained. Using nonprobability consecutive sampling technique, this study was conducted on 104 pediatric patients admitted to Children B Unit with blood culture-proven enteric fever. Data was collected from blood cultures and sensitivity reports from the microbiology section of our hospital laboratory. This study was conducted on 32 female and 72 male pediatric in-patients with blood culture-proven enteric fever caused by Salmonella typhi. Resistance to Azithromycin was 43.26%, Meropenem 17.30%, Polymixin 13.46%, Colistin 31.73%, Tigecycline, 01.92%, Imipenem 04.80% Salmonella typhi demonstrated high levels of resistance to commonly used antibiotics.